Amblyraja georgiana, Antarctic Starry Skate - Pollom, R.; Acuña, E.; Bustamante, C.; Chiaramonte, Gustavo Enrique; Cuevas, J.M.; Herman, K.; Pompert, J.; Velez Zuazo, X.
The Antarctic Starry Skate (Amblyraja georgiana) is a medium-sized (to 115 cm total length) deepwater skate that occurs in the Southeast Pacific Ocean off southern Chile, in the Southwest Atlantic Ocean off southern Argentina and the Falkland Islands (Malvinas), in the Atlantic and Pacific Antarctic Oceans from South Georgia Island and the Antarctic Peninsula to the Ross Sea, and in the Indian Antarctic off the Crozet Islands. It is demersal on continental and insular slopes at depths of 20?1,255 m, and is captured as bycatch in trawl and longline fisheries, particularly those targeting Patagonian Toothfish (Dissostichus eleginoides). There are no population size estimates for this skate, and it is not clear what the current population trend is. Although estimates of bycatch around South Georgia and the Ross Sea are comprised of a low percentage of overall estimated stock biomass, the demographic consequences are unknown and require further research. Furthermore, catch levels in other areas are unknown, and some specimens previously referred to as this species may include cryptic individuals of a yet-to-be-described species. Overall, it is not clear what level of fishing mortality this species is exposed to across its range, and further research is needed on distribution, population size and trend, and threats. Therefore, the Antarctic Starry Skate is assessed as Data Deficient. Fil: Pollom, R. University Fraser Simon; Canadá Fil: Acuña, E. Universidad Católica del Norte; Chile Fil: Bustamante, C. Universidad de Antofagasta; Chile Fil: Chiaramonte, Gustavo Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia". Estación Hidrobiológica de Puerto Quequén (sede Quequén); Argentina Fil: Cuevas, J.M. Wildlife Conservation Society; Estados Unidos Fil: Herman, K. Georgia Aquarium; Estados Unidos Fil: Pompert, J. No especifíca; Fil: Velez Zuazo, X. No especifíca;